2016
DOI: 10.4172/2169-0022.1000244
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Point Pinning Centers in Un-Doped Mgb2 Wires at 20 K after HIP Process

Abstract: In this paper we present results of transport critical current density (J c ) at 20 K and 4.2 K, irreversible magnetic field (B irr ), upper critical field (B c2 ), critical temperature (T c ), pinning force (F p ), scanning pinning force scaling results (F p /F pmax and B/B irr ) and electron microscope (SEM) images of un-doped MgB 2 wires of 0.63 mm diameter. All wires were annealed at pressures ranging from 0.1 MPa to 1 GPa for 15 min between 680°C to 740°C. SEM images show that 1 GPa pressure yields small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This is confirmed by the study of Serquis et al 18 We believe that this effect decreases the T c and the critical parameters above 25 K and increases the critical parameters below 16 K. Based on the results in Fig. 2 and the results for the undoped MgB 2 wires, 19 we can deduce that a higher level of C doping and a higher pressure will cause a further reduction of critical parameters at higher temperatures (20 K-39 K). This indicates that a pressure of 1 GPa and a small amount of dopant are the optimum conditions.…”
Section: Fig 1(a)supporting
confidence: 76%
See 2 more Smart Citations
“…This is confirmed by the study of Serquis et al 18 We believe that this effect decreases the T c and the critical parameters above 25 K and increases the critical parameters below 16 K. Based on the results in Fig. 2 and the results for the undoped MgB 2 wires, 19 we can deduce that a higher level of C doping and a higher pressure will cause a further reduction of critical parameters at higher temperatures (20 K-39 K). This indicates that a pressure of 1 GPa and a small amount of dopant are the optimum conditions.…”
Section: Fig 1(a)supporting
confidence: 76%
“…It also leads to a reduction in the T c . Our study on the undoped MgB 2 wires showed that 1 GPa pressure decreases the T c by 1.5 K, increases the critical parameters in the range of 10 K to 27 K, and decreases the critical parameters above 27 K. 19 The similar influence of the isostatic pressure to that of C doping on the T c may indicate that the isostatic pressure creates a lattice distortion. This is confirmed by the study of Serquis et al 18 We believe that this effect decreases the T c and the critical parameters above 25 K and increases the critical parameters below 16 K. Based on the results in Fig.…”
Section: Fig 1(a)mentioning
confidence: 52%
See 1 more Smart Citation